Транскордонне природоохоронне співробітництво України та країн Європейського Союзу - Бортник, Сергій Юрійович; Лаврук, Тетяна Миколаївна; Тимуляк, Любов Миколаївна; Омельчук, Т.І. (Київський національний університет імені Тараса Шевченка, 2018)
У статті проаналізовано досвід міжнародного співробітництва у розвитку транскордонних природоохоронних територій України та країн ЄС на прикладі біосферного резервату «Східні Карпати». Подано характеристику організації та функціонування національних природних парків Ужанського, Бещадського та «Полонини». Проведено аналіз природоохоронної діяльності в межах цих об’єктів ПЗФ та пропонується запозичення досвіду для розвитку української частини біосферного резервату та інших транскордонних природоохоронних територій.

The experience of internationalcooperation in the development of transboundary nature conservation territories of Ukraine and the EUcountries on the example of the Eastern Carpathians biosphere reserve was analyised in article. Thecharacteristic of the organization and functioning national nature parks of Uzhansky, Bieschadsky andPoloniny is given.The assessment of environmental activities within these objects was conducted and it was suggested toborrow some provisions of international experience for the development in Ukrainian part of the EasternCarpathians biosphere reserve, as well as for other transboundary nature conservation territories. It isnecessary to organize scientific research work, to initiate educational and volunteer programs on nature conservation, to exchange experience of international environmental work. Important in this case will be theopening and equipment of international tourist and nature trails, a dense network of which has long existed inEurope.Problems of scientific substantiation of the expansion of existing protected territories, as well as planningnew, the organization of an independent transboundary monitoring of the state of ecosystems are particularlyrelevant to all transboundary regions of Ukraine.For the Carpathian region the problems of control over illegal felling in the Uzhansky National Park, theobservance of the environmental regime of certain massifs of the Carpathian Biosphere Reserve, theproliferation of the reserve regime of the Svydovets massif for the whole Basin of the Chorna Tysa river arevery important. More attention should be paid to the preservation of ethnographic features of the Carpathians,the development of ecological consciousness of local inhabitants and the population of Ukraine as a whole,their responsibility for the preservation of unique national natural conditions and resources.The solution of the above problems to a large extent depends on the geographers who should participatedirectly in the study and planning of the development of transboundary protected areas.Only through joint efforts of international cooperation Ukraine's naturally reserved fund will become amultifunctional part of the Pan-European ecological network.Keywords: transboundary nature protection cooperation, Ukraine, European Union countries,transboundary biosphere reserves, Pan-European ecological network.
Transboundary Nature Conservation Cooperation between Ukraine and the Countries of the European Union
Keywords: транскордонне природоохоронне співробітництво; транскордонні біосферні резервати; пан’європейська екологічна мережа; Україна; країни Європейського Союзу; transboundary nature protection cooperation; Ukraine; European Union countries; transboundary biosphere reserves; Pan-European ecological network